Nostalgia in the Poetry of the Kings and Leaders in Andalusia - Aissa Faris; Tallal Ali Deyoub (دراسات فی اللغه العربیه و آدابها)
Nostalgia is a tendency of conscience include humanitarian all ages and at all times. It is an expression of sincere desire of poet to see the motherland where he was established, and where requirements of life forced him to abandon it. Associated poems of the kings and leaders in Andalusia set in political circumstances and social self, deepened their sense of sorrow and regret for the loss of splendor, combined with sovereignty and power, and activated nostalgic feelings for the anticipated return, to convenience, luxury life and the grace. This study investigates the poems which kings and leaders sang in nostalgia, and handles them in the light of the psychological, social conditions and self-raised these emotional feelings It also deals with delicate sensations in the class of these poets who expressed through nostalgia two contradictory elements oin the elegance of the past. Under some extreme conditions that have occurred in their lives, they missed the grace of communication with their parents, relatives, and their places, and their emotions began flowing honestly from their depths, puffing it in an exhale under the difficult conditions in which they live. Nostalia for the Homeland includes nostalgic poems of kings and leaders, as we will see in their selected poems. Unlike religious poems, nostalgia in the poems of poet Minister Lisan Din Ibn al-Khatib merges the past and the future.